Opini Audit, Dana Perimbangan, Kondisi Keuangan dan Pengungkapan Informasi Keuangan Pemerintah Daerah - Putri, Errina Aprilia; Rahayu, Sri; Lestari, Tri Utami (E-Jurnal Akuntansi, 2022)
This study aims to determine the effect of audit opinions, balancing funds, and financial conditions on the disclosure of local government financial information, especially on the official website owned. This research is a quantitative study that uses secondary data from the financial statements of 34 Indonesian provincial governments for the 2019-2020 period as many as 68 samples. The analysis in this study used logistic regression analysis with SPSS 26. The results showed that audit opinion and financial condition had no effect on the disclosure of local government financial information. Balancing funds have a negative effect on the disclosure of local government financial information. Keywords: Audit Opinion; Intergovernmental Revenue; Financial Condition; Disclosure of Local Government Financial Information